Peripheral T-Cell Lymphoma Coexisting with Autoimmune Hemolytic Anemia: Analysis of Clinical Features - DEMİRTAŞ, DERYA; YANIK, AHMET MERT; YILMAZ, ASU FERGÜN; ATAGÜNDÜZ, IŞIK; TUĞLULAR, AYŞE TÜLİN; TOPTAŞ, TAYFUR (My University, 2024)
Autoimmune hemolytic anemia (AIHA) is characterized by the production of antibodies targeting red blood cells (RBCs) antigens. The diagnosis is based on the presence of a hemolytic anemia with a positive direct antiglobulin test (or Coombs test) and on the absence of any other hereditary or acquired cause of hemolysis, although direct antiglobulin test-negative cases are not quite uncommon (5% of 308 cases of AIHA recently reported by the Gruppo Italiano Malattie EMatologiche dell’Adulto [GIMEMA]) [1, 2]. AIHA can present in primary and secondary forms. Secondary AIHA generally includes factors such as connective tissue diseases, drugs, infections, and lymphomas [3]. Cases of AIHA accompanied by lymphoma are rare and are typically presented in the literature as case reports. Roughly one-fifth of AIHA patients have lymphoma, while 7–10% of lymphoma patients have co-existing AIHA, indicating a clinicopathological link between both diseases [4–6]. In clinical settings, AIHA is commonly associated with indolent B-cell lymphomas, whereas the combination of AIHA with peripheral T-cell lymphoma (PTCL) is rarely observed [7–11]. This study retrospectively analyzes the clinical data, laboratory characteristics, treatment processes, and prognosis of five patients with the coexistence of PTCL and AIHA who were diagnosed within the last 10 years in our center.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEMATOLOGY